Mupirocin ointments: In vitro x In vivo bioequivalence evaluation - Stephanye Carolyne Christino Chagas; Camila de Almeida Perez Pimenta; Juliana Kishishita; Irla Carla França Barbosa; Danilo Cesar Galindo Bedor; Katia Aparecida da Silva Aquino; Davi Pereira de Santana; Leila Bastos Leal (Universidade de São Paulo, 2022)
Abstract Bioequivalence (BE) assessment of topical drug products is a long-standing challenge. Agencies such as the Food and Drug Administration (FDA) and the European Medicines Agency (EMA) have published several drafts in recent years suggesting different approaches as alternative to evaluate the BE. A proposed Topical Classification System (TCS) has even been discussed. Given the above, the objective of this research was to use in vitro and in vivo BE approaches to evaluate Brazilian marketed mupirocin (MPC) ointments, previously classified as TCS class The in vitro permeation test (IVPT) was performed by applying formulations to pig skin by Franz cells. The in vivo methodology was dermatopharmacokinetic (DPK). These approaches (in vivo tape stripping and IVPT) demonstrated capability of distinguishing among different formulations, thus making them useful methodologies for BE evaluation.